Developing a Medical Institution Management System through Promoting Social Accountability; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Plotnikova I. V. Inna Vasilievna; Kurmanbek kyzy Nurzat; Redko L. A. Lyudmila Anatolevna; Shadrina O. A. Olga; Yanushevskaya M. N. Marina Nikolaevna (2017, 2017)
Title screen